Distance effects and product feature differentiation in a tourism duopoly. (26th February 2015) - Ou, Shih-Ming; Chang, Ching; Lee, Yao-Hsien
Many tourism companies in Taiwan's tourism industry expect themselves to be unique in the market by means of developing featured products. Besides, they have to face the impact of distance effects on tourists' destination choice. In our research, we argue that the effect of friction of geographic distance discourage tourists to visit the tourism destination, while cognitive proximity plays the role of increasing interactions between tourism companies and their potential tourists. To acquire a better understanding of the relationship between proximity investment sizes and pricing, we employ the three-stage game approach and endogenous spillovers to discuss the differentiation strategies adopted by two competitive companies. Accordingly, we provide solutions to the three managerial problems including featured product design, increasing cognitive proximity investment size, and pricing. We also show that spillover effect is the decisive factor in tourism companies' investment decisions.